In situ observations of coral spawning and spawn slick at Lankayan Island, Sabah, Malaysia - Gan, S.H.,; Zarinah Waheed; Chung, F.C.,; Spiji, D.A.,; Sikim, L.,; Ejria Saleh; Tan, C.H. (Springer Science and Business Media Deutschland GmbH, 2021)
Sexual reproduction of corals is one of the most important processes for the persistence of coral populations. The Coral Triangle is recognised as a global hotspot of marine biodiversity, harbouring 75% of the world coral species. However, coral reproductive studies remain underrepresented in many reefs in the Coral Triangle. This study reports the coral spawning and spawn slicks occurrences from 2012 to 2019 at Lankayan Island, Malaysia, a small island located in the Sulu Sea at the westernmost boundary of the Coral Triangle. A total of 14 species belonging to three genera and two families were recorded to spawn on the reefs between March and May in 2012–2015 and 2019. Between one and eight species spawned on each observed spawning night. Acropora corals appear to dominate the spawning events based on direct observations on the reefs. Coral-spawn slicks were observed during March to May every year and in October 2019. We observed coral spawning between March and May in Lankayan Island, similar to other localities within the Coral Triangle. © 2021, Senckenberg Gesellschaft für Naturforschung.